ChemInform Abstract: Synthesis of Alkyl 3‐Chloroazetidine‐3‐carboxylates via Regioselective Ring Transformation of Alkyl 2‐(Bromomethyl)aziridine‐2‐carboxylates. Issue 20 (20th May 2014) - De Kimpe, Norbert; Zukauskaite, Asta; Mangelinckx, Sven; Sackus, Algirdas
Abstract 4 Title compounds of type (III) are prepared via regioselective ring transformation of aziridine carboxylates (I).